Key agreement based secure Kerberos authentication protocol (KASKAP) for distributed database access in secured manner - M, Natarajan; R, Manimegalai (International Journal of Engineering and Technology, 2018)
Distributed database is a collection of multiple databases that can be stored at different network sites. It acts as an important role in today’s world intended for storing and retrieving huge data. The implementation of distributed database advantages such as data replication, low operating costs, faster data transaction and data processing, but security is still a significant problem. In this paper make clear to explain security issues of distributed database and give the suggestion to improve security of distributed database. Subsequently, secured distributed database design in light of trusted node is proposed. The design contains a unique node in a system called a trusted node for each site through which every single other node will get to the database. Trusted node process client demands, joins the outcomes from concerned distributed databases and forward it to the confirmed client. The system adjusted by the trusted nodes keeping in mind the end goal to give authentication is Key Agreement based Secure Kerberos Authentication Protocol (KASKAP). Hence authenticated users can only access the database.